Populational alteration of cells in the intestinal intraepithelial layer and morphological changes of the intestinal wall elicited by Toxocara vitulorum infection in buffalo calves (Bubalus bubalis) - Neves, Maria Francisca; Starke-Buzetti, Wilma A (My University, 2005)
To understand the development of the inflammatory responses in the wall of the gut, during the process of expulsion of the parasites from the host, samples of tissues were removed from the small intestines from four groups of naturally infected buffalo calves with Toxocara vitulorum during the beginning of the infection, at the peak of egg output, during the period of expulsion and post-expulsion of the worms, as well as from uninfected calves. Cells (mast cells, eosinophils, intraepithelial lymphocytes - IEL and goblet cells) present in the epithelial layer (intraepithelial) of the small intestine were counted. In the duodenum, jejunum and ileum, the population of mast cells, eosinophils and lymphocytes increased significantly during the peak of the infection. Goblet cell numbers increased also during the beginning and at the peak of the infection. The decline of the number of these cells occurred during the periods of expulsion of the worms reaching to uninfected control counts at the post-expulsion period indicating a role of these cells in the process of expulsion of T. vitulorum by the buffalo calves. The layers of the intestinal wall (villus, crypt, submucosa and muscular) were also measured. Morphological examinations showed a significant vilar atrophy, particularly in the duodenum during the beginning, peak and during the period of expulsion of the worms, but smooth muscle hypertrophy or other alteration was not observed in any period of the infection.
Alteração populacional de células na camada intraepitelial e alterações morfológicas da parede intestinal causada pela infecção por Toxocara vitulorum en bezerros Búfalos (Bubalus Bubalis).